Prey preference of checkered beetle, Callimerus arcufer (COLEOPTERA: CLERIDAE) - Azlina Zakaria,; Meor Badli Shah Ahmad Rafie,; Samsudin Amit,; Nur Azura Adam,; Rita Muhamad Awang,; Idris Ab Ghani, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Oil palm Lepidopteran species were reported to attack oil palm, which caused substantial crop loss. The biological control approach is mainly the encouragement of natural enemies’ population build-up, including insect predators, which will result in the natural suppression of the Lepidopteran pest population. There is insufficient evidence on the preference of insect predator, Callimerus arcufer Chalpin (Coleoptera: Cleridae) against Lepidopteran leaf defoliators, hence this study determined the prey species preference of C. arcufer. The experiment was conducted through choice and non-choice prey acceptability by C. arcufer at constant densities of different Lepidopteran prey species. When the predator was not given choices of prey, the predator consumed all prey species given, with an insignificant difference in percentage consumed. The predator, however, has a significantly higher preference towards both bagworm species, Metisa plana, and Pteroma pendula compared to other Lepidopteran species tested, implying that C. arcufer could be an important predator species for oil palm bagworm, and could sustain in the environment when its main food source is inadequate.